Interventions to improve mental well-being and sleep in paramedics: A scoping review - Sian E. Wanstall; Brandon W. J. Brown; Meagan E. Crowther; Claire Dunbar; Robert J. Adams; Anjum Naweed; Amy C. Reynolds (PLoS ONE, 2026)
Background Paramedics face unique occupational hazards, including high operational demands, trauma exposure, and shift work, all of which impact mental well-being. Suboptimal sleep is also common in this workforce and closely linked to adverse mental health outcomes. This scoping review synthesizes evidence to date on interventions to support paramedic mental well-being including sleep-based interventions. Materials and methods This review was pre-registered on the Open Science Framework ( https://doi.org/10.17605/OSF.IO/7VSD9 ). Systematic database searches were conducted in October 2024 for original research published after 2004. Data were narratively synthesised, and findings reported following established guidelines. Results Nineteen sources were included, involving 1,067 participants across seven countries. Seventeen interventions were examined, predominantly via randomized controlled trials (58%), utilizing a total of 43 different measurement scales to evaluate mental health and sleep outcomes. Interventions included psychological (37%), sleep, fatigue and/or shift work (32%), and complementary and alternative medicine (32%) approaches which primarily focussed on the individual-level (94%). Studies were limited by sample sizes, design and quality, limited long term follow-up, and low baseline symptoms. Conclusions This review highlights a critical gap in robust, evidence-based, system-level interventions to address poor sleep and mental well-being in paramedics. Future research should prioritise co-designed, context-sensitive approaches, ideally integrated within organisational structures to ensure relevance and accessibility.